Upaya Peningkatan Hasil Belajar Tematik IPA Melalui Penerapan Model PBL pada Siswa Kelas V SDN 1 Tegaljadi Tahun Pelajaran 2022/2023 - Yastuti, Ni Wayan Winarti; Utami, Linda Sekar; Suheriyantini, Suheriyantini; Hasan, Baiq Harlin (Universitas Pendidikan Mandalika, 2023)
Tujuan dari penelitian ini adalah meningkatkan hasil belajar siswa pada mata Pelajaran IPA dengan menggunakan model pembelajran PBL. Metode yang digunakan adalah Metode PTK yang terdiri dari 2 siklus pembelajaran. Subjjek penelitian terdiri dari 15 siswa. Hasil belajar tematik IPA peserta didik kelas V SD Negeri 1 Tegaljadi dengan model pembelajaran Problem Beased Learning pada tema 1 muatan IPA mengalami peningkatan yaitu dari pra siklus dengan nilai rata-rata 62,67% dengan ketuntasan belajar klasikal meningkat menjadi 70 pada siklus 1, dan pada siklus II rata-rata nilai peserta didik meningkat menjadi 81.3% dengan kategori tinggi dan berhasil mencapai indikator ketuntasan belajar sebesar 86.67 %. Kesimpulannya dengan model PBL dapat meningkatkan hasil belajar siswa.Efforts to Improve Thematic Science Learning Outcomes Through the Implementation of the Problem-Based Learning (PBL) Model in Grade V Students of SDN 1 Tegaljadi Academic Year 2022/2023AbstractThe aim of this research is to enhance students' learning outcomes in the subject of Science using the Problem-Based Learning (PBL) instructional model. The research employed the Classroom Action Research (PTK) method, conducted in two learning cycles, with a total of 15 student participants. The thematic Science learning outcomes of fifth-grade students at SD Negeri 1 Tegaljadi, utilizing the Problem-Based Learning model in the first thematic topic of Science, demonstrated improvement. The pre-cycle average score was 62.67%, and the classical mastery learning increased to 70 in the first cycle. In the second cycle, the average student scores further improved to 81.3%, falling under the high category, and successfully achieving a mastery learning indicator of 86.67%. In conclusion, the implementation of the PBL model contributed to the enhancement of students' learning outcomes.